Ionospheric flow shear associated with the preexisting auroral arc: A statistical study from the FAST spacecraft data. Issue 6 (24th June 2015) - Jiang, Feifei; Kivelson, Margaret G.; Strangeway, Robert J.; Khurana, Krishan K.; Walker, Raymond
Abstract An auroral substorm is a disturbance in the magnetosphere that releases energy stored in the magnetotail into the high‐latitude ionosphere. By definition, an auroral substorm commences when a discrete auroral arc brightens and subsequently expands poleward and azimuthally. The arc that brightens is usually the most equatorward of several auroral arcs that remain quiescent for 5 to 60 min before the breakup commences. This arc is often referred to as the "preexisting auroral arc (PAA)" or the "growth‐phase arc." In this study, we use FAST measurements to establish the statistics of flow patterns near PAAs in the ionosphere. We find that flow shear is present in the vicinity of a preexisting arc. When a PAA appears in the evening sector, enhanced westward flow develops equatorward of the arc, whereas when a PAA appears in the morning sector, enhanced eastward flow develops poleward of the arc. We benchmark locations of the PAAs relative to large‐scale field‐aligned currents (FACs) and convective flows in the ionosphere, finding that the arc forms in the upward current region within 1° of the Region 1/Region 2 boundary in all local time sectors from 20 MLT to 03 MLT. We also find that near midnight in the Harang region, most of the PAAs lie within 0.5° poleward of the low‐latitude Region 1/Region 2 currents boundary and sit between the westward and eastward flow peak but equatorward of the flow reversal point. Finally, we examine arc‐associated electrodynamics and find that the FAC of the PAA is mainly closed by the north‐south Pedersen current in the ionosphere.